MEMBAGUN DEMOKRASI BERKEADABAN DAN DINAMIKA PEMILIHAN PRESIDEN LANGSUNG 2019 - Hadi Karyono (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
Building democracy is not something easy, democracy as a political system has become the choice of our founding fathers. Democracy to this day is still considered to be the best political system of the political system that has ever existed. As the best political system, democracy must be cared for and fostered in order to thrive in our country, the Republic of Indonesia. However, at present, there are many efforts that distort democracy. SARA politics developed by certain groups for example. Besides the hoax news that is repeatedly spread so that it is considered a truth. This ultimately made people including millennials confused. This paper aims to explore more deeply how to build a democratic democracy and the dynamics of the 2019 presidential election. In this paper the literature research method is used. In the discussion it can be concluded that the challenge of the 2019 general election is: how to deal with challenges ahead of the 2019 general election in Indonesia to implement an effective political constellation to build political stability.